(untitled) (The Review of Diabetic Studies, 2024)
Background: Family medicine clinics are central to primary health care, providing comprehensive and continuous services that directly influence patient satisfaction and service quality. Nursing leadership within these settings plays a pivotal role in shaping care delivery, fostering team collaboration, and enhancing patient experiences. While global evidence supports the positive impact of effective nursing leadership, research specific to Saudi Arabia remains limited. Objectives: To map and synthesize existing evidence on the impact of nursing leadership in family medicine clinics on patient satisfaction and service quality, and to identify implications for the Saudi Arabian health care context. Methods: A scoping review was conducted following Arksey and O’Malley’s framework, enhanced by Levac et al., and reported according to PRISMA-ScR guidelines. Five databases (PubMed, CINAHL, Scopus, Web of Science, Cochrane Library) were searched without date restrictions for studies in English or Arabic. Eligible studies included quantitative, qualitative, mixed-methods research, and relevant systematic reviews that examined nursing leadership in family medicine or primary care settings with outcomes related to patient satisfaction or service quality. Data were extracted and synthesized narratively, with thematic analysis identifying key patterns and contextual factors. Results: Of 760 records identified, 31 studies met the inclusion criteria. Most studies reported positive associations between effective nursing leadership—particularly transformational, empowerment-focused, and collaborative styles—and improved patient satisfaction, communication, and service quality metrics. Distributed leadership models were also effective in enhancing care coordination and patient trust. Studies from Saudi Arabia and the Middle East highlighted the influence of organizational culture, hierarchical structures, and gender dynamics on leadership practices. Conclusions: Effective nursing leadership in family medicine clinics is strongly linked to higher patient satisfaction and better service quality. However, there is a notable lack of Saudi-specific empirical research. Policy initiatives should focus on leadership training, empowering nurse leaders in decision-making, promoting interdisciplinary collaboration, and aligning leadership development with Saudi Vision 2030 health care transformation goals